High Electron Mobility Thin‐Film Transistors Based on Solution‐Processed Semiconducting Metal Oxide Heterojunctions and Quasi‐Superlattices. Issue 7 (26th May 2015) - Lin, Yen‐Hung; Faber, Hendrik; Labram, John G.; Stratakis, Emmanuel; Sygellou, Labrini; Kymakis, Emmanuel; Hastas, Nikolaos A.; Li, Ruipeng; Zhao, Kui; Amassian, Aram; Treat, Neil D.; McLachlan, Martyn; et al.
<x xml:space="preserve">Abstract</x> High mobility thin‐film transistor technologies that can be implemented using simple and inexpensive fabrication methods are in great demand because of their applicability in a wide range of emerging optoelectronics. Here, a novel concept of thin‐film transistors is reported that exploits the enhanced electron transport properties of low‐dimensional polycrystalline heterojunctions and quasi‐superlattices (QSLs) consisting of alternating layers of In2O3, Ga2O3, and ZnO grown by sequential spin casting of different precursors in air at low temperatures (180–200 °C). Optimized prototype QSL transistors exhibit band‐like transport with electron mobilities approximately a tenfold greater (25–45 cm2 V−1 s−1) than single oxide devices (typically 2–5 cm2 V−1 s−1). Based on temperature‐dependent electron transport and capacitance‐voltage measurements, it is argued that the enhanced performance arises from the presence of quasi 2D electron gas‐like systems formed at the carefully engineered oxide heterointerfaces. The QSL transistor concept proposed here can in principle extend to a range of other oxide material systems and deposition methods (sputtering, atomic layer deposition, spray pyrolysis, roll‐to‐roll, etc.) and can be seen as an extremely promising technology for application in next‐generation large area optoelectronics such as ultrahigh definition optical displays and large‐area microelectronics where high performance is a key requirement.